2021
DOI: 10.1177/10608265211035941
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Gender Competency with Men in Mind: Foundations of an Online Training Program for Mental Health Practitioners

Abstract: Recognition of the importance of mental health practitioners’ enactment of ‘gender competency’ when working with men is growing. This article describes the development and theoretical background to a novel online training program for practitioners, called Men in Mind. The training focuses on men’s gender socialization, engaging male clients in therapy, and responding effectively to men’s depression and suicidality. The content of the training was derived from a comprehensive review of available literature, str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 71 publications
2
14
0
Order By: Relevance
“…Men in Mind is an online training program for mental health practitioners working with men [ 28 ]. Development, creation, and hosting of the training program was funded by Movember, the world’s largest men’s health charity.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Men in Mind is an online training program for mental health practitioners working with men [ 28 ]. Development, creation, and hosting of the training program was funded by Movember, the world’s largest men’s health charity.…”
Section: Methodsmentioning
confidence: 99%
“…The five training program modules are structured around key domains derived from reviews of the literature [ 7 , 20 ] and qualitative research with help-seeking men [ 11 ] and practitioners [ 17 ]. The development and theoretical background to the training program is described in depth elsewhere [ 28 ]. Pilot evaluation of the Men in Mind training, conducted in early 2021, found that the training program demonstrated acceptability, feasibility and potential efficacy in a sample of 196 practitioners [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…To address this knowledge gap, global men’s health charity Movember funded the development and testing of a five-module, self-paced online training program to upskill mental health practitioners in male-specific adaptations to therapy. Called Men in Mind, this interactive course draws learning outcomes and core content from empirical literature on how to best engage men in therapy (Seidler, Wilson, Owen, et al, 2021). With a theoretical underpinning in Connell’s (2005) gender relations work focused on hegemonic masculinity alongside plural masculinities and diversity among men, Men in Mind broadly explores the relational aspects of the client’s and practitioner’s gender constructions and their interaction in-session.…”
mentioning
confidence: 99%
“…The findings have several practical implications. First, the findings underscore a need for enhanced training for helpline counsellors around male-specific presentations of distress and how to effectively engage with and support male callers, as is underway in the therapy space [ 50 , 51 ]. Any such efforts should be underpinned by evidence and involve co-design elements with men who have a lived experience of helpline use to maximise their impact potential.…”
Section: Discussionmentioning
confidence: 99%